Validation and Psychometric Properties of the Farsi Version of the Parental Psychological Control Scale - Ahmad Baindrian; Ali Khodaei; Omid Shokri (روانشناسی بالینی و شخصیت)
Introduction: Parents are the primary agents of socialization for children and adolescents. The significant role of parenting in this process has garnered considerable attention among researchers, making it a key area of study. Among the various parenting strategies, parental psychological control has attracted particular interest. Consequently, this study aims to psychometrically analyze the Persian version of the Parental Psychological Control Scale. Method:  This descriptive survey study involved 300 adolescents who were selected using a convenience sampling method. Participants responded to the Parental Psychological Control Scale (Zhou, Du, & Pan, 2023), the Empowering Parenting Scale (Jack, Sun, Luton, Chin, & Waters, 2018), and the short version of the Cognitive Emotion Regulation Questionnaire (Garnofsky & Kraij, 2006). The study conducted by Zhou et al. (2023) utilized exploratory and confirmatory statistical methods on independent samples of adolescents, which empirically supported a structure comprising three aspects: communicative induction, harsh psychological control, and shame resulting from social comparison.Results: The results of the confirmatory factor analysis indicated that the Parental Psychological Control Scale, which comprises three factors—communicative induction, harsh psychological control, and shame stemming from social comparison—demonstrated good factor validity. Furthermore, the correlations between the dimensions of parental psychological control and empowering parenting, as well as adaptive and maladaptive cognitive emotion regulation strategies in adolescents, supported the convergent validity of the Persian version of the Parental Psychological Control Scale. The internal consistency coefficients for the subscales of communicative induction, harsh psychological control, and social comparison shame were 0.88, 0.80, and 0.77, respectively.Discussion and conclusion: Overall, the validation of the Persian version of the Parental Psychological Control Scale provided further evidence supporting the multidimensional nature of parental psychological control and the culturally dependent conceptualizations of its subscales.